Numerical study on the cavity dynamics for vertical water entries of twin spheres - Wang, Xu; Lyu, Xujian; Sun, Ruisheng; Tang, Dongdong (Defence technology, 2024)
In this study, a three dimensional (3D) numerical model of six-degrees-of-freedom (6DOF) is applied to simulate the water entries of twin spheres side-by-side at different lateral distances and time intervals. The turbulence structure is described using the shear-stress transport k-ω (SST k-ω) model, and the volume of fluid (VOF) method is used to track the complex air-liquid interface. The motion of spheres during water entry is simulated using an independent overset grid. The numerical model is verified by comparing the cavity evolution results from simulations and experiments. Numerical results reveal that the time interval between the twin water entries evidently affects cavity expansion and contraction behaviors in the radial direction. However, this influence is significantly weakened by increasing the lateral distance between the two spheres. In synchronous water entries, pressure is reduced on the midline of two cavities during surface closure, which is directly related to the cavity volume. The evolution of vortexes inside the two cavities is analyzed using a velocity vector field, which is affected by the lateral distance and time interval of water entries.